Desarrollo de un entorno virtual 3d de un proceso batch para la distribución de alimentos de una granja aplicando una comunicación tcp/ip - Pullopaxi Lema, Fredy Rene (2022)
The purpose of this technological proposal is to develop a 3D virtual environment based on a feed distribution system for birds through a batch process, which will be simulated in a specified virtual reality software, in turn will be executed using TCP/ IP. The implementation of this system is based on ON-OFF level controllers, which will be coded in a physical programmable controller, so the programming will be previously loaded into the PLC in order to achieve a uniform distribution of the food within the batch process. , this procedure will be monitored through the virtual environment and in turn through indicators in an HMI system. The development of this environment allows the user to record and acquire level data for subsequent system analysis. Through the TCP/IP communication protocol, bidirectional data transmission is achieved so that the user can have manual and automatic control of the process. With the execution of this project, the students of the electromechanical engineering career can develop practices that allow them to strengthen their automation skills.